EFFECT OF E-RECRUITMENT ON THE EFFECTIVENESS OF EMPLOYEE RECRUITMENT - Rumangkit, Stefanus; Dwiyan, Muhammad (Prosiding International conference on Information Technology and Business (ICITB), 2018)
This study aims to examine the effect of E-Recruitment on employee recruitment effectiveness. This research is a quantitative research, with a questionnaire as a method of data collection. Questionnaires were distributed to 300 respondents. The sampling technique uses purposive sampling, with the criteria of respondents is generation Z, born in 1995-2010. Data analysis tools use simple linear regression. The results of this study found that E-recruitment affects the effectiveness of employee recruitment. This shows that when a company uses technology, one of them is E-recruitment, then job seekers will be interested in using the facility. Thus, companies can obtain candidates with a very large number of workers and have the opportunity to get the best competent employees.Keywords : E-Recruitment, Effectiveness Of Employee, Generation Z